THE EFFECT OF ISLAMIC SOCIAL REPORTING (ISR) DISCLOSURE AND PROFITABILITY ON COMPANY VALUE : (Empirical Study of Companies Listed in the Jakarta Islamic Index for the 2018-2020 Period) - Winarsih, Winarsih (Fakultas Ekonomi, 2024)
Company value is an indicator of how the market assesses the company as a whole. A high company value is the desire of shareholders, because a high value shows that their prosperity is also high. The aim of this research is to test the influence of the variables Islamic Social Reporting, ROA Profitability, ROE Profitability on company value as proxied by PBV (Price Book Value). The population in this research are companies registered on the Jakarta Islamic Index for the 2018-2020 period. A total of 28 companies were used as samples using purposive sampling techniques. The analysis technique used in this research is Multiple Linear Regression. The results of this research indicate that Islamic Social Reporting (ISR) has no effect on company value. Return on Assets (ROA) profitability has no effect on company value. Profitability Return on Equity (ROE) has a significant effect on company value.